Rituximab in kidney disease and transplant. Issue 2 (26th March 2019) - Chauhan, Kajal; Mehta, Anita A.
Abstract: Rituximab is a chimeric monoclonal antibody that binds to CD20 antigen of B‐cells. It depletes the level of mature B‐cells by various mechanisms such as mediation of antibody‐dependent cellular cytotoxicity, complement‐dependent cytotoxicity, and B‐cell apoptosis. Rituximab is a USFDA approved drug for clinical use in non‐Hodgkin's B‐cell lymphoma (NHL), rheumatoid arthritis, chronic lymphocytic leukemia (CLL), granulomatosis with polyangiitis and pemphigus vulgaris. It is also known for its "off label" use in renal disease and renal transplant worldwide. However, the exact mechanisms by which it exerts its effect in the aforementioned condition remain unclear but may be related to its long‐term effects on plasma cell development and the impact on B‐cell modulation of T cell responses. This review discusses the current use of rituximab in renal disease and renal transplantation, and its potential role in novel therapeutic protocols.